Haplotype effects on matrix metalloproteinase-1 gene promoter activity in cancer cells - Pearce, Eve G.; Laxton, Ross C.; Pereira, Andresa C.; Ye, Shu (American Association for Cancer Research (AACR), 2007)
Increased expression of matrix metalloproteinase-1 (MMP1) is associated with poor prognosis in cancers. Several single nucleotide polymorphisms (-1607GG > G, -839G > A, -755G > T, -519A > G, -422T > A, -340C > T, and 320C > T) in the MMP1 gene promoter have recently been identified. In this study, we assessed the functional effects of these polymorphisms on MMP1 gene promoter activity in cell lines of melanoma (A2058 and A375), breast cancer (MCF7 and MDA-MB-231), lung cancer (A549 and H69), and colorectal cancer (HT-29, SW-620) by comparing the promoter strengths of 10 most common haplotypes deriving from these polymorphisms. In A2058 cells, the GG-G-G-A-T-T-T and GG-G-G-A-C-T haplotypes had 2-fold higher promoter activity than the GG-G-T-A-T-T-C, GG-G-G-A-A-T-T, GG-G-G-A-T-T-C, and GG-G-G-A-A-C-T haplotypes, which in turn, had 3-fold higher promoter activity than the G-G-T-A-A-C-T, G-A-T-G-T-T-T, G-A-T-G-A-C-T, and G-A-T-G-A-T-G haplotypes. In A375 and MDA-MB-231 cells, high expression haplotypes include not only the -1607GG-bearing haplotypes but also the G-A-T-G-A-T-T haplotype containing the -1607G allele. A similar trend was detected in A549 cells. In addition, in A549 cells, the GG-G-G-A-T-T-T haplotype had > 2-fold higher promoter activity than several other 1607GG-bearing haplotypes. In MCF7 cells, the GG-G-G-A-T-T-T and G-G-T-A-A-C-T haplotypes had 1.5- to 4-fold higher promoter activity than the other haplotypes. These results suggest that the polymorphisms exert haplotype effects on the transcriptional regulation of the MMP1 gene in cancer cells, and indicate a need to examine haplotypes rather than any single polymorphism in genetic epidemiologic studies of the MMP1 gene in cancers.